سعيد يقطين ناقدا ثقافيا، السيرة الشعبية نموذجا - بن عطية, نصر الدين; قريش, بنعلي (جامعة الوادي - university of Eloued, 2021)
يتناول هذا البحث جهود سعيد يقطين في دراسة التراث السردي العربي عامة والسيرة الشعبية خاصة، فقد استطاع أن ينقل هذا المهمش من اللانصية إلى النصية بعدما غيبت نقديا في النقد العربي القديم فلم يلتفت إليها لأمور متصلة بالمؤسسة الأدبية الرسمية التي حاولت جهدها خنق كل محاولة أدبية لا توافق هواها، وإخضاع الحياة لأطرها الثابتة على الرغم من الرواج الكبير بين المتلقين على اختلاف أوساطهم وثقافاتهم. هذا المكون الرئيس كاشف عن ثقافة مسكوت عنها حيدت رسميا على مدى قرون ولكنها استطاعت كسر القيود من حولها لتفرض وجودها خاصة مع الدراسات الثقافية والنقد الثقافي. This research deals with the efforts of Said Yaktine in studying the Arab narrative heritage in general and the popular biography in particular. and He was able to transfer this margin of inhumanity to the text after absent criticism in the old Arab criticism did not pay attention to things related to the official literary institution, which tried to stifle every literary attempt does not like it, And subjecting life to its fixed frameworks despite the great popularity among recipients of different media and cultures. This major component has revealed a culture that has been officially abandoned for centuries, but has managed to break the restrictions around it to impose its existence, especially with cultural studies and cultural criticism.
مقال
Keywords: النقد الثقافي. السيرة الشعبية. النص. اللانص. التراث